Walt Whitman, Poetry and Care - José Siles González (Universidad de Alicante, 2016)
To understand the impact of Whitman in the poetry and sociopoetics of care is essential to know the environment in which the American poet improvised developed his work as a nurse in a historical context marked by a bitter civil war. Only in this way you can grasp the interaction between his poetry, his person and his work as a nurse. In this editorial, the author analyzes the most significant works of the author in relation to their impact with his experience as a caregiver : Leaves of Grass" and drum-Taps".